Performance of Supercritical CO2 Power Cycle and Its Turbomachinery with the Printed Circuit Heat Exchanger with Straight and Zigzag Channels - Muhammed Saeed; Khaled Alawadi; Sung Chul Kim (Energies, 2020)
Since printed circuit heat exchangers (PCHE) are the largest modules of a supercritical carbon dioxide Brayton cycle, they can considerably affect the whole system’s performance and layout. Straight-channel and zigzag-channel printed circuit heat exchangers have frequently been analyzed in the standalone mode and repeatedly proposed for <semantics>sCO2−BC</semantics>. However, the impact of heat exchanger designs with straight and zigzag-channel configurations on the performance of the cycle and its components, i.e., the turbine and compressor, has not been studied. In this context, this study evaluates the effect of different heat exchanger designs with various values of effectiveness (<semantics>ϵ</semantics>), inlet Reynolds number (Re), and channel configuration (zigzag and straight channel) on the overall performance of the <semantics>sCO2−BC</semantics> and its components. For the design and analysis of PCHEs, an in-house PCHE design and analysis code (PCHE-DAC) was developed in the MATLAB environment. The <semantics>sCO2−BC</semantics> performance was evaluated utilizing an in-house cycle simulation and analysis code (CSAC) that employs the heat exchanger design code as a subroutine. The results suggest that pressure drop in PCHEs with straight-channel configuration is up to 3.0 times larger than in PCHEs with zigzag-channel configuration. It was found that a higher pressure drop in the PCHEs with straight channels can be attributed to substantially longer channel lengths required for these designs (up to 4.1 times than zigzag-channels) based on the poor heat transfer characteristics associated with these channel geometries. Thus, cycle layouts using PCHEs with a straight-channel configuration impart a much higher load (up to 1.13 times) on the recompression compressor, this in turn, results in a lower pressure ratio across the turbine. Therefore, the overall performance of the <semantics>sCO2−BC</semantics> using PCHEs with straight-channel configurations is found to be substantially inferior to that of layouts using PCHEs with zigzag-channel configurations. Finally, optimization results suggest that heat exchanger’s design with inlet Reynolds number and heat exchanger effectiveness ranging from <semantics>32 k</semantics> to <semantics>42 k</semantics> and <semantics>0.94>ϵ>0.87</semantics>, respectively, are optimal for <semantics>sCO2−BC</semantics> and present a good bargain between cycle efficiency and its layout size.